ANALISIS PENGARUH PENGHARGAAN DAN PENGEMBANGAN KARIER TERHADAP RETENSI KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING (Studi pada Karyawan Perum LPPNPI AirNav Indonesia Kota Tangerang) - Disa, Laksmita Zhafira; Djastuti, Indi (Diponegoro Journal of Management, 2019)
This study aims to determine and analyze the influence of reward and career development variables on employee retention through job satisfaction as an intervening variable in General Company of Aviation Navigation Service Provider (Perum LPPNPI) or better known as AirNav Indonesia. The population used in this study are employees with a work period of more than 1 year and have minimum education level of diploma/academy. The amount of samples used in this study were 155 respondent.In this study, data was collected through the distribution of questionnaires on samples selected through non-probability sampling techniques with purposive sampling method. Measurements in the questionnaires using a Likert Scale. Five hypotheses were tested using quantitative methods and data analysis technique using Structural Equation Modelling (SEM) analysis with AMOS 21.0 software.The testing result of hypothesis shows that causality relationship between the influenced variables with Goodness of Fit criteria, such as Chi-square = 212,329; Significance Probability = 0,068; CMIN/DF = 1,160; GFI = 0,888; AGFI = 0,858; TLI = 0,983; NFI = 0,904; CFI = 0,985 and RMSEA = 0,032. The result shows that reward has a positive and significant effect on job satisfaction. Career development has a positive and significant effect on job satisfaction. Reward has a positive and significant effect on employee retention. Career development has a positive and significant effect on employee retention. Job satisfaction has a positive and significant effect on employee retention. This research also shows that there is no mediating effect of job satisfaction to the effect of reward on employee retention, but job satisfaction successfully mediates the relationship between career development and employee retention.